Water Quality of Bagmati River in Kathmandu Valley, Nepal - Acharya, Dhruba; Pant, Bhoj Raj (Saptagandaki Journal, 2021)
Abstract Background: Water quality degradation is one of the major challenges especially in under developed and developing countries and Nepal is no exception from it. Adequate water quality and quantity is one of the greatest factors affecting human and ecosystem health, and is essential for socio-economic growth and the improvement in the quality of life. This study aims to assess the water quality of Bagmati River in Kathmandu, the capital city of federal Nepal. Methods: Water quality of the Bagmati River in Kathmandu Valley was analyzed to assess the river water pollution. A total ten sites from Sundarijal to Sundarighat along the Bagmati river corroder was selected for sample collection. The samples were analyzed for physical (pH, Temperature, Conductivity), and chemical (dissolved oxygen, oxygen saturation percentage, biological oxygen demand, chloride, nitrate-N, phosphate-P and ammonia-N) parameters in pre-monsoon and post-monsoon seasons using standard methods. Results: The result reveals that water quality of the Bagmati River has degraded due to physical, chemical and biological contaminants. Discharge of untreated sewers, industrial effluents, unmanaged location of solid waste transfer station, dumping and burning of plastic waste and garbage near to the river bank. In both the season pollution was found to be increasing from upstream to downstream as indicated by Bach water quality index. The paired sample t-test of physicochemical parameters in two different seasons showed that all tested parameter were significantly different except dissolved oxygen and phosphate concentration. parameters pH, range between 7.55 to 6.33, temperature 30 °C to 26.23 °C, electrical conductivity 43.73 µS/ cm to 810.5 µS/cm, dissolved oxygen 0 mg/L to 9.52 mg/L, oxygen saturation percentage 0 to 119.75 %, biological oxygen demand 2 mg/L to 400 mg/L, chloride 4.97mg/L to 132.54mg/L, nitrate-N 9 mg/L to 110 mg/L, phosphate-P 0.26 mg/L to 2.95 mg/L and ammonia-N range between 0.41 mg/L to 42 mg/L. Conclusion: Untreated sewerage, industrial effluents, dumping and burning of waste, unmanaged location of solid waste transfer stations, poor management of cremation ash has resulted in the excessive water pollution in Bagmati river. Treatment of waste water before discharge to the river and proper management of cremation ash and garbage, and prevention of illegal dumping of solid waste and burning of garbage and plastic materials along the river can alleviate the water pollution in Bagmati river.